Universal Driver CD-ROM : graphics & expansion cards - Universal... (Soltek Computer Inc, 2003)
Besar file 600 MB, berisi file program : acrobat, ATI, detonator, directX, directX9, Nvidia, USB20, Xabre, dan Soltek.exe.